2022
DOI: 10.1515/biol-2022-0495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structural, oxidative, and immunological features of testis tissue from Zucker diabetic fatty rats

Abstract: The purpose of this study was to characterize the testicular profile of Zucker diabetic fatty (ZDF) rats presenting with type 2 diabetes mellitus (DM2) in the absence or presence of obesity. To achieve this, testes were collected from 270-day-old male Wistar (n = 15), ZDF nonobese (n = 15), and ZDF obese rats (n = 16). Changes to the testicular structure were quantified morphometrically, while immunocytochemistry was employed to assess caspase-3 activity. Reactive oxygen species (ROS) production, fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 78 publications
6
13
0
Order By: Relevance
“…Alterations to testicular architecture are a common side effect of chronically elevated blood sugar or excessive accumulation of body fat. In accordance with our morphometric analysis in the untreated animals, previous reports observed that the induction of diabetes through medication or increased feed intake led to a reduced germ cell count and abnormalities to the spermatogenic series [22,23,29,30]. In particular, ZDF obese controls presented with a reduced cell layer with contracted and/or disarranged spermatogenic cells in the seminiferous tubules.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Alterations to testicular architecture are a common side effect of chronically elevated blood sugar or excessive accumulation of body fat. In accordance with our morphometric analysis in the untreated animals, previous reports observed that the induction of diabetes through medication or increased feed intake led to a reduced germ cell count and abnormalities to the spermatogenic series [22,23,29,30]. In particular, ZDF obese controls presented with a reduced cell layer with contracted and/or disarranged spermatogenic cells in the seminiferous tubules.…”
Section: Discussionsupporting
confidence: 90%
“…A reduced testicular weight in the Obese control observed in this study corroborates previous reports on diabetic rats [22][23][24] and may be explained by the loss of germ cells, inhibition of spermatogenesis, or a decline in the activity of steroidogenic enzymes necessary for a proper sperm production [23,25,26]. In the meantime, the testicular weights were increased following QUE supplementation in both experimental groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations